2020
DOI: 10.3390/geosciences10080278
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Structure of Zircon from Hydrothermal Uranium Occurrences of the Litsa Ore Area (Kola Region, Russia)

Abstract: Zircon grains from various metagranitoids (plagio- and monzo-granites, gneisses, metasomatic rocks, and pegmatoid veins) from the Skal’noe and Dikoe sites of the Litsa uranium ore area (Kola Region, Russia) were studied in order to reconstruct the sequence and timing of events in the area and to observe effects of hydrothermal process related to uranium mineralization on structure and composition of zircon. Individual zircon grains were studied by means of laser ablation inductively coupled plasma mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…The 1002-1009 cm −1 band is attributed to the ν 3 stretching mode of SiO 4 tetrahedra, while the ν 1 mode was observed at 970-974 cm −1 . Another internal mode was identified at 437-440 cm −1 that was assigned to the ν 2 bending vibration [18,48,49,53,54]. The 352-358 cm −1 line was previously assigned to the ν 4 bending mode [55], but more detailed studies based on group-theory analysis of the total number of Raman-active modes and structural investigations concluded that this line is due to external rotational modes of SiO 4 [18,48,49,53].…”
Section: Zirconmentioning
confidence: 96%
“…The 1002-1009 cm −1 band is attributed to the ν 3 stretching mode of SiO 4 tetrahedra, while the ν 1 mode was observed at 970-974 cm −1 . Another internal mode was identified at 437-440 cm −1 that was assigned to the ν 2 bending vibration [18,48,49,53,54]. The 352-358 cm −1 line was previously assigned to the ν 4 bending mode [55], but more detailed studies based on group-theory analysis of the total number of Raman-active modes and structural investigations concluded that this line is due to external rotational modes of SiO 4 [18,48,49,53].…”
Section: Zirconmentioning
confidence: 96%
“…Наблюдаемое занижение степени кристалличности (величина рамановского сдвига пика ν 3 (SiO 4 ) существенно меньше ожидаемой для соответствующей величины альфа-дозы − серые точки на рис. 10, а), вероятно, отражает высокую степень гидротермальной переработки пород[Kaulina et al, 2017]. При дальнейших вычислениях анализы с заниженными оценками степени кристалличности во внимание не принимались.Статистически значимое (20-30 %) количество зерен, подвергавшихся термическому отжигу, зафиксировано в трех пробах из верхнепермского интервала: Zh-11 (разрез Жуков овраг), A-10 и А-4 (разрез Асташиха).…”
unclassified